Vitamin D equilibrium affects sex-specific changes in lipid concentrations during Christian Orthodox fasting. Issue 211 (July 2021) - Karras, Spyridon N.; Koufakis, Theocharis; Dimakopoulos, Georgios; Adamidou, Lilian; Karalazou, Paraskevi; Thisiadou, Katerina; Bais, Alkiviadis; Tzotzas, Themistoklis; Manthou, Eleni; Makedou, Kali; Kotsa, Kalliopi
Highlights: 45 healthy Orthodox fasters (24 females) were prospectively followed for 12 weeks. Anthropometry, vitamin D and lipid levels were assessed before and after fasting. We observed sex-specific lipid responses to a low-fat diet associated with vitamin D status. Abstract: We aimed to evaluate sex differences in changes of lipid profiles in a cohort of metabolically healthy adults following Orthodox fasting (OF), as well as to assess a potential role of vitamin D status in mediating these variations. 45 individuals (24 premenopausal females, 53.3 %) with mean age 48.3 ± 9.1 years and mean Body Mass Index 28.7 ± 5.8 kg/m 2 were prospectively followed for 12 weeks. Anthropometry, dietary and biochemical data regarding serum lipids, and vitamin D status were collected at baseline, 7 weeks after the implementation of OF, and 5 weeks after fasters returned to their standard dietary habits (12 weeks from baseline). According to 25-hydroxy-vitamin D [25(OH)D] measurements, participants were divided into two groups: those with concentrations above and below the median of values. Females with 25(OH)D concentrations below the median manifested a non-significant reduction by approximately 15 % in total and low-density lipoprotein cholesterol during the fasting period, followed by a significant increase 5 weeks after OF cessation (170.7 vs. 197.5 and 99.6 vs. 121.0 mg/dl respectively, p < 0.001). In contrast, males with 25(OH)D levels below the median demonstrated an inverse, non-significant trend of increase in lipid concentrations during the whole study period. Our findings suggest strikingly different inter-gender lipid responses to a dietary model of low-fat, mediated by vitamin D status. Further studies are necessary to reveal the underlying mechanisms and assess the importance of these differences with respect to cardiovascular health and the benefit of vitamin D supplementation strategies.